Re(con)figuring Psychoanalysis
XV, 283 p.
Keywords: Leading international scholars present novel dialogues between different psychoanalytic orientations as well as between the particularities of diverse socio-cultural and historical contexts in order to offer critical insights which are highly relevant to the current intellectual debates and social praxis.